Prevalence and management of familial hypercholesterolemia in patients with coronary artery disease: The heredity survey. (1st February 2018) - Faggiano, Pompilio; Pirillo, Angela; Griffo, Raffaele; Ambrosetti, Marco; Pedretti, Roberto; Scorcu, Giampaolo; Werren, Marika; Febo, Oreste; Malfatto, Gabriella; Favretto, Giuseppe; Sarullo, Filippo; Antonini-Canterin, Francesco; et al.
Abstract: Background and aims: Familial hypercholesterolemia (FH) is a genetic disorder characterized by high levels of low density lipoprotein cholesterol (LDL-C) predisposing to premature cardiovascular disease. Its prevalence varies and has been estimated around 1 in 200–500. The Heredity survey evaluated the prevalence of potential FH and the therapeutic approaches among patients with established coronary artery disease (CAD) or peripheral artery disease (PAD) in which it is less well documented. Methods: Data were collected in patients admitted to programs of rehabilitation and secondary prevention in Italy. Potential FH was estimated using Dutch Lipid Clinic Network (DLCN) criteria. Potential FH was defined as having a total score ≥ 6. Results: Among the 1438 consecutive patients evaluated, the prevalence of potential FH was 3.7%. The prevalence was inversely related to age, with a putative prevalence of 1:10 in those with < 55 yrs of age (male) and < 60 yrs (female). Definite FH (DLCN score > 8) had the highest percentages of patients after an ACS (75% vs 52.5% in the whole study population). At discharge, most patients were on high intensity statin therapy, but despite this, potential FH group still had a higher percentage of patients with LDL-C levels not at target and having a distance from the target higher than 50%. Conclusions: Among patients with established coronary heart disease, the prevalence of potential FH is higher than in the general population; the results suggest that a correct identification of potential FH, especially in younger patients, may help to better manage their high cardiovascular risk.